Strategi Menanggulangi Kesulitan Belajar Moral Dan Karakter Di Sekolah Dasar Dengan Menggunakan Metode Pendidikan Moral - Anita Yulia Safitri; Nur Hidayah Huba; Rihadatul Aisyah; Andien Afriannisa; Latifah Hikmalia Rahma; Ranggita Dwi Syahla; Muhammad Azhar Nawawi; Ika Yatri (Departement of Mathematics Education, 2024)
When it comes to molding the personalities of primary school kids, moral and character education is paramount. To produce a morally upright next generation, it is crucial that children grow up in a morally upright society, and schools play a significant role in this process, second only to families in this regard. The moral principles imparted, however, are frequently misunderstood by the students. The media, inadequate instructional methods, and the home environment are all contributors to these learning disabilities. By setting a good example themselves, using effective teaching tactics, and paying close attention to pupils who are struggling academically, teachers can help their students overcome these challenges. To help primary school students overcome these obstacles to learning, this article explores numerous approaches to moral and character education. Using a literature review strategy, this research employs a descriptive qualitative technique. The findings demonstrate that students can absorb moral and character values through the work of educators, parent-school partnerships, and the use of instructional strategies like project-based learning, moral dilemmas, and role-playing.